Ronggeng: Genealogi Perempuan Penari Dari Masa Kolonial Hingga Era Mutakhir - S.Sn., M.Sn., Masyuning; Atang Suryaman; Pepep Didin Wahyudin (Paraguna, 2025)
In the current discourse of performing arts, ronggéng has been specified or narrowed down to mean only female dancers. The opposite of ronggéng is known as "pamogoran" or men from the audience who join in the dancing and also give money to the ronggéng. Based on a phenomenological perspective with a discussion of interactive time boundaries, combining synchronic and diachronic time boundaries, it can be concluded that historically, the female body in Ronggéng's identity has been distorted since colonialism. Ronggéng, which is synonymous with a sacred body in the life of an agrarian society, has been drawn into the industrial dimension by the interests of colonialism. Since then, a new image has been created that is synonymous with a negative stigma towards the bodies of women dancers, especially Ronggéng, which is associated with sexuality. In recent times, female dancers have emerged who "fight" against this stigma by making themselves not only a manageable dancer, but metamorphosing into a dancer as well as a leader, creating new dance ideas.